Singapore's Land Transport Authority (LTA): A Case Study of Predictive AI and Centralized Coordination in Urban Traffic Management - Guo, Hanxiang; Leong, Wa Yie (INTI International University, 2025)
This study examines Singapore’s Smart Mobility strategy through the predictive and centralized system operated by the Land Transport Authority (LTA). Using the four-dimensional ITS framework including data acquisition, network connectivity, analytical intelligence, and operational responsiveness, the paper evaluates how predictive artificial intelligence and integrated control systems contribute to urban traffic management. The study finds that Singapore’s centralized, predictive governance model has led to notable improvements in average expressway speed, bus punctuality, and incident clearance times. However, limitations remain in areas such as system adaptability and data transparency. Comparative discussion with international cities offers insight into the scalability and constraints of such predictive transport systems.